Latency of epoxide hydratase and its relationship to that of udpglucuronyltransferase - Burchell, B.; Bentley, P.; Oesch, F. (Biochimica et biophysica acta, 1976)
Epoxide hydratase activity in liver microsomal preparations from adult male rats is latent to a slight extent. Maximal activations with neutral or anionic detergents were 30–60% whilst UDPglucuronyltransferase was maximally activated by 160–830% by the same detergents. Activation of microsomal epoxide hydratase requires much higher amounts of neutral or anionic detergents than activation of microsomal UDPglucuronyltransferase. High concentrations of inorganic salt, sonication or freeze-thawing which activate microsomal UDPglucuronyltransferase have no influence on microsomal epoxide hydratase activity. From this it appears that the activation which may involve either removal of a permeability barrier or release from conformational restraint occurs more easily for UDPglucuronyltransferase than for epoxide hydratase and that the activation of microsomal epoxide hydratase requires breakage of some hydrophobic bonds between the enzyme and membrane components(s).